A new approach for study the electrohydrodynamic oscillatory flow through a porous medium in a heating compliant channel - Haroun, Mohamed H. (Zielona Góra: Uniwersytet Zielonogórski)
The governing equations of an electrohydrodynamic oscillatory flow were simplified, using appropriate non-dimensional quantities and the conversion relationships between fixed and moving frame coordinates. The obtained system of equations is solved analytically by using the regular perturbation method with a small wave number.
Keywords: oscillatory flow; electrohydrodynamic; porous medium; heat transfer; compliant channel